Evaluation of Biological Activated Carbon (BAC) process in wastewater treatment secondary effluent for reclamation purposes - MERTOĞLU, BÜLENT; KALKAN AKTAN, ÇİĞDEM; AKGÜL, DENİZ; BAKIRCI, KOZET (ELSEVIER SCIENCE BV, 2011)
The effects of two different granular activated carbon (GAC) types (steam activated, PK1-3 and chemically activated, CAgran) on dissolved organic carbon (DOC) removal. nitrification and denitrification were evaluated in BAC columns for wastewater reclamation/reuse purposes. Continuous-flow laboratory-scale BAC columns were operated for 320 days using the secondary effluent water of Pasakoy Advanced Wastewater Treatment Plant. During the first 83 days of column operation, when adsorption was the dominant mechanism, the average DOC removal efficiency was 81% for PK1-3 and 64.5% for CAgran. Later on, the efficiencies dropped to 45.9% for PK 1-3 and 37.8% for CAgran. which shows the operational time period when breakthrough is reached and DOC removal is dominantly due to biodegradation. BAC columns were also capable of removing total nitrogen; removal efficiencies were observed to be 54.0% for the biofilter packed with PK1-3 and 51.5% for the one packed with CAgran. The results also showed that DOC and ammonia nitrogen concentrations immediately decrease due to dilution and biodegradation at the top of the BAC columns. This study establishes that a carefully operated BAC system, which was used for tertiary treatment of a secondary effluent, can remove organic carbon and total nitrogen to a significant extent. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Biological Activated Carbon (BAC); Water reclamation; Biodegradation; Nitrification; Denitrification; ULTRAVIOLET DISINFECTION; PERFORMANCE; FILTERS; NITRIFICATION; FILTRATION; ADSORPTION; REUSE; BIOFILTRATION; OZONATION; REACTORS